2011
DOI: 10.1007/s10384-011-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Honan intraocular pressure reducer on intraocular pressure increase following intravitreal injection using the tunneled scleral technique

Abstract: The use of the HIPR reduces the IOP after an intravitreal injection using the tunneled scleral technique. However, the HIPR does not appear to affect a reduction in the vitreous reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…These findings resonate with the results of Kim and Jee who demonstrated that the Honan intraocular pressure reducer, applied to the eye at 30 mmHg for 10 minutes, significantly lowered pre-injection IOP and IOP immediately after intravitreal injection using tunneled scleral technique. 12 The IOP at 10 minutes post-injection was lower in the Honan group as well. The Honan balloon is a bulky and awkward device, which takes significantly greater time than the current method, and carries a risk of producing extremely high IOPs in eyes with higher initial pressure, such as in patients with glaucoma.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These findings resonate with the results of Kim and Jee who demonstrated that the Honan intraocular pressure reducer, applied to the eye at 30 mmHg for 10 minutes, significantly lowered pre-injection IOP and IOP immediately after intravitreal injection using tunneled scleral technique. 12 The IOP at 10 minutes post-injection was lower in the Honan group as well. The Honan balloon is a bulky and awkward device, which takes significantly greater time than the current method, and carries a risk of producing extremely high IOPs in eyes with higher initial pressure, such as in patients with glaucoma.…”
Section: Discussionmentioning
confidence: 83%
“…The Honan balloon is a bulky and awkward device, which takes significantly greater time than the current method, and carries a risk of producing extremely high IOPs in eyes with higher initial pressure, such as in patients with glaucoma. 12 Therefore, other ways of decompressing the eye, such as gentle pressure with cotton swabs saturated with an anesthetic, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 65% of studies (n=44/67) were retrospective in design with follow-up periods of more than 6 months reported in less than a third (n=18/67) of included studies. Baseline characteristics of participants were comparable in two non-randomised studies28 29 and three case-control studies 30–32…”
Section: Resultsmentioning
confidence: 99%
“…In addition to monitoring the amount of postinjection reflux, other groups have also suggested lowering preinjection IOP with glaucoma drops 27 or softening the eye with pressure during anesthetic preparation of the globe 28,29 to reduce the levels of immediate postinjection IOP. Based on our analysis, the presence of a PVD increased the likelihood of postinjection reflux.…”
Section: Discussionmentioning
confidence: 99%